Disappoint Me - Dinan, Nicola (New York, NY : The Dial Press, 2025)
""Fell down the stairs and woke up a trad wife." Max is thirty, a published poet and grossly overpaid legal counsel for a tech company. With a lifetime of dysphoria and fuccbois rattling around in her head, Max is plagued with a deep dissatisfaction during what should be the best years of her life. After taking a spill down the stairs at a New Year's Eve party, she decides to make some changes. First things first: a stab at good old-fashioned heteronormativity. Max thinks she's found the answer in Vincent, a corporate lawyer and hobby baker, whose trad friendship group may as well speak a foreign language, and whose Chinese parents never pictured their son dating a trans woman. This uncharted territory may have rough terrain, but Vincent cares for Max in a way she'd long given up on as a foolish fantasy. Yet Vincent is carrying his own baggage from his gap year in Thailand a decade prior: an explosive entanglement with a mysterious, gorgeous traveler. Voice-driven, warm, and poignant, Disappoint Me is an exploration of millennial angst, race, trans panic, and the allure of bourgeois domesticity that asks if we are defined by our worst mistakes"--.
new book 2025 spring.
Keywords: Transgender women -- Fiction; Dating (Social customs); Romance fiction; Transgender fiction; Psychological fiction; LGBTQ+ people; Women; Transgender fiction; Novels; Romance fiction